Laws, Statutes, Ordinances, and Constitutions 39 (John Holt ed., 1763) - (:unkn) unknown (My University, 1763)
no person or persons whatsoever inhabiting within the said city, within two miles of the city-hall of the said city, shall presume to keep in any house, shop, cellar, store-house, or other place within the said city (his majesty's garrison and magazine only excepted) any more or greater quantity of gunpowder at one time, than twenty-eight pounds weight (except in the magazines or powder house aforesaid) under the penalty of ten pounds current money of New York, for every offense.
Keywords: GUNPOWDER - STORAGE